8. THE IMPORTANCE OF AIR DEFENSE SYSTEM IN THE MODERN WARFARE: THE CASE OF RUSSIA’S AIR SUPERIORITY IN SYRIA: THE IMPORTANCE OF AIR DEFENSE SYSTEM IN THE MODERN WARFARE - furqon; Kurniawan; Tia Dikatama Tsania; Militia Christi Pandelaki; Anak Agung Banyu Perwita; Budi Pramono (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2025)
This study aims to determine the extent to which the most strategic area as Russian air defense. The Eastern Mediterranean region is now the most strategic area for the advancement of Russian air defense. After its intervention in the Syrian theater, Russia seems to be able to maintain its military footprint by deploying an integrated surveillance system that has succeeded in inviting world attention to the development of A2/AD (anti access/area denial) capabilities. Russia seems to have ensured the improvement of war technology with its involvement in the Syrian war. By becoming the boss of the Syrian airspace, Russia also took the opportunity to conduct some military training in actual combat experience. Thus, this article then finds that from the perspective of military improvement and refinement, the Russian military presence is in the most advantageous position in relation to the opportunity to use the permissive environment of Syria. Overall, this article believes that the emergence and continuation of Russian military action in the global arena will always be rooted in its threat perception towards the Western tribe.